Abstract Number ‐ 147: Rescue bailout repair of a direct carotid‐cavernous fistula using drug eluding coronary stent - Amrinder Singh; Yahia M Lodi (Stroke: Vascular and Interventional Neurology, 2023)
Introduction Direct carotid‐cavernous fistula (DCCF) during neurosurgical procedures or trauma are repaired with flow diverters via trans‐arterial approach and/or transvenous embolization of the cavernous sinus. There are reports of using balloon mounted bare platinum coronary stent in the treatment of DCCF prior to the era flow diverters. There are limited data on the use of drug eluding stent in the repair of DCCF. We are presenting an unusual case of DCCF developed during Neurointerventiona in an acute ischemic stroke patient with severe intracranial atherosclerotic disease that was emergently repaired using a Medtronic resolute prelude drug eluding. Additionally, cause of DCCF and rational of balloon drug eluding stent was expalined. Methods case report Results 54 years old women with multiple cerebrovascular risk factors including prior stroke presented with right middle cerebral artery (MCA) stroke which improved to NIHSS 2. CT head demonstrated old strokes in the right MCA distributions and CT angiogram was consistent with severe intracranial atherosclerotic disease (ICAD) with 90% stenosis of right supraclynoid internal carotid artery (SICA). Patient was loaded with brilinta and aspirin. Cerebral angiogram confirmed focal ICAD and presence of ahteresclorotic pouches (AP) at the Pero‐cavernous junction with poor perfusion. Parent artery diameter was 2.2 mm and stenotic section 0.5 mm. Planned was to do balloon angioplasty and a possible stent. Endovascular strategies: 6 French guiding sheath was placed to RICA and CAT5 to protect ICA pouches, and be placed beyond the ophthalmic artery for navigation of balloon delivery system. Baseline activated coagulation time (ACT) was 168 and received 4000 units of heparin with 5 mg of intraarterial integrilin. During advancement of 2×20 mm maverick balloon, the CAT5 prolapsed back below the petrous ICA. Attempts were made to reposition the CAT5 over the wire without microcatheter resulting in injury to the AP with CAT5 forming DCCF. Immediately, balloon was navigated without manipulation of CAT5 and angioplasty of SICA with reduction of stenosis from 90% to less than 50%. Repeat angiogram demonstrated high‐flow DCCF. Because of ICAD and small ICA diameter, a flow‐diverter was not considered. A Medtronic resolute drug eluding 2×34 mm stent was advanced emergently through CAT5 and placed the injured area by withdrawing CAT5 and deployment of resulting in good apposition. Subsequent angiographies revealed gradual decrease of DCCF to complete obliteration. Repeat ACT was above 400 which was not reversed. Neurological examination remained unchanged without ophthalmic sign of DCCF. Patient was sent home in 48 hours with NIHSS 0 on brilinta and aspirin. Conclusions A flexible Medtronic resolute drug eluding could be used emergently to repair traumatic DCCF which is delivered over CAT5. An intermediate guiding catheter CAT5 or others must be advanced over a microcatheter alone with microwire carefully to prevent vessel injury especially, if there are existing disease in the wall of the artery. Brilinta load may potentially increase the baseline ACT, therefore a small bolus of heparin may be considered first if the baseline ACT is high to prevent supratherapeutic ACT. Further studies are required